Efektivitas Polietilen Glikol sebagai Bahan Penyeleksi Kedelai Kipas Merah Bireun yang Diradiasi Sinar Gamma untuk Toleransi terhadap Cekaman Kekeringan - Zuyasna Zuyasna; Effendi Effendi; Chairunnas Chairunnas; Arwin Arwin (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
Polyethylene Glycole Effectivity as Selection Agent to Soybean: Kipas Merah from Bireun Radiated with Gamma Ray for Drought Stress Tolerance ABSTRACT. The purpose of this research is to know the effectivity of Polytethylene Glycole (PEG) in drought simulation in vitro to soybean – Kipas Merah from Bireun – radiated with gamma ray. Research was conducted in Tissue Culture Laboratory, Agriculture Faculty, Syiah Kuala University, Darussalam, Banda Aceh. Gamma ray radiation conducted at Research Development of Isotop and Radiation Technology of BATAN, Pasar Jum`at, Jakarta. The results show that increasing in PEG concentration into selection medium in vitro, decrease soybean seed germination percentage. Twenty percent of PEG concentration can be use as sub lethal concentration for the next drought selection attempt. Gamma ray radiation cause variation to seed germination percentage and seed growth in vitro.